Immunohistochemical labelling of components of the endoneurial extracellular matrix of intact and rhizotomized dorsal and ventral spinal roots of the rat--a quantitative evaluation using image analysis - Jančálek, Radim; Dubový, Petr (Acta histochemica, 2006)
The endoneurial extracellular matrix (ECM) molecules are involved in cell signalling during nervous system development and regeneration. Quantitative differences of immunofluorescence labelling for chondroitin sulfate proteoglycan (CSPG), fibronectin (FN), tenascin-C (TN-C), and thrombospondin (TSP) were evaluated in intact rat dorsal and ventral roots and dorsal and ventral roots 2 and 4 weeks after rhizotomy using image analysis. The distal stumps of spinal roots displayed increased immunolabelling for the molecules with higher immunofluorescence in dorsal than in ventral roots up to 2 weeks from transection. Four weeks after rhizotomy, the immunoreactivity for CSPG, TN-C and TSP decreased in dorsal and increased in ventral root stumps, although a higher level of immunofluorescence for FN remained in both dorsal and ventral root stumps 4 weeks after injury in comparison to 2 weeks after injury. We suggest that the amount of some ECM molecules changed differentially 2 and 4 weeks after rhizotomy to create an appropriate environment in the endoneurium for early and later regrowth of sensory and motor axons. The results presented here are the first report of differences between the endoneurial ECM content of damaged afferent and motor nerve fibers. In addition, the immunohistochemical detection of individual ECM molecules indicated that final extrinsic conditions stimulating the regrowth of regenerating axons probably arise from a balance of both growth-promoting and -inhibiting molecules in the endoneurium.
Keywords: Motor Neurons; fluorescenční protilátková technika nepřímá; fibronektiny; regenerace nervu; Rats, Wistar; Tenascin; tenascin; Peripheral Nerves; rizotomie; Image Processing, Computer-Assisted; imunohistochemie; Fluorescent Antibody Technique, Indirect; potkani Wistar; Chondroitin Sulfate Proteoglycans; krysa rodu Rattus; Neurons, Afferent; počítačové zpracování obrazu; Animals; ženské pohlaví; Immunohistochemistry; Nerve Regeneration; zvířata; Rats; kryoultramikrotomie; chondroitinsulfát proteoglykany; Financing, Organized; motorické neurony; Cryoultramicrotomy; neurony aferentní; Fibronectins; Female; míšní kořeny; periferní nervy; financování organizované; Rhizotomy; Spinal Nerve Roots